Productive potential of yellow passion fruit irrigated with wastewater (Research, Society and Development, 2020)
Water reuse is a viable alternative environmentally and economically in agricultural production. In this context, the objective was to evaluate the productivity of the yellow passion fruit, as well as the changes provided in the soil due to different levels of replacement of the evapotranspiration of the crop, using treated domestic sewage and well water as water sources. The experiment was carried out in a randomized block design (DBC) with a split plot scheme with four replications. The plots consisted of two water sources (treated domestic sewage effluent and artesian well water) and, in the subplots, five irrigation depths based on the evapotranspiration of the crop (50; 75; 100; 125 and 150% of ETc). The fresh weight of the fruit and fruit diameter increased significantly due to the use of well water as a water source. The increase in water availability provided increases in the number of fruits and in the average productivity of the crop. The use of treated domestic sewage effluent did not promote undesirable changes in the evaluated chemical parameters, enabling satisfactory and environmentally viable productivity, and may even partially replace chemical fertilization.